Web-Based Interactive Learning Media Integrated with Soft Skills ‎for Network System Administration in Vocational High Schools - Anggi Alfioni; Anas Arfandi; Mukhlisin (Yayasan Darussalam Bengkulu, 2026)
Vocational high schools are expected to prepare students with technical competence and employability-oriented soft skills. However, learning in Network System Administration often remains dominated by teacher explanation, static materials, and assessments that focus mainly on technical knowledge and final scores. This study developed and evaluated a web-based interactive learning medium integrated with soft skills for vocational high school students. Using a Research and Development approach, the study synthesized the 4D, ADDIE, and Borg and Gall models into seven stages: needs analysis, design, development, testing and revision, implementation, evaluation and final revision, and dissemination and adoption. Data were collected through observation, interviews, expert validation sheets, student-response questionnaires, and pretest-posttest learning outcome tests. The product consisted of learning objectives, interactive materials, video resources, quizzes, automated feedback, project tasks, evaluation results, and soft-skill activities covering character, citizenship, collaboration, communication, creativity, and critical thinking. Expert validation indicated that the product was highly feasible, with mean scores of 93.50% from material experts and 90.73% from media experts. Practicality testing showed progressive improvement from 69.00% in one-to-one trials to 74.00% in small-group trials and 84.00% in field trials. The effectiveness test showed that the experimental class achieved a higher mean gain than the control class, 29.47 compared with 3.00. The posttest comparison was statistically significant, t(58) = 2.44, p = .018, with a medium effect size, Cohen’s d = .63. These findings suggest that web-based interactive media can enhance technical understanding while supporting soft-skill-oriented vocational learning in more meaningful and engaging classroom contexts.